Balanced Business Decision-making for Clinical Practices: Fulfilling “Mission” and “Margin” - Rajiv Chandawarkar, MD, MBA; Prakash Nadkarni, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Clinical practices, both private and academic, need to be profitable to sustain themselves and grow. To manage them and drive profits, one needs leadership that has a well-rounded understanding of multiple facets. When business decisions are based on financial data alone, they meet the goal of profit margin but alienate clinicians; when made using clinical data alone, they fulfill the clinical mission but ignore the bottom line. Here, we explain the benefits of a sound business-minded leadership that integrates the nuances of financial data, the cadence of clinical practices, and the value of resources, and makes meaningful business decisions. These decisions create a strong bond between physicians and their administrative leaders, aligning their “mission” (provide better care), and their “margin” (profitability and growth). We explain critical aspects of each source of information and how to use them together to make business decisions. Recognizing that clinicians may not have access to methods of financial analysis, we also supply a prepopulated Excel spreadsheet that has all equations baked in, so that it can be readily used, filling in their own data to generate financial ratios. This work explains how sound decisions can be made using financial metrics, clinical data (here, plastic surgery), and resource utilization, to identify areas that can be improved and take steps to achieve results.